The effect of extrusion with molasses and addition of chitosan or tannins on the rumen undegradable protein fraction of plant protein sources - Jordaan, Leanne (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.